Original paperComparison of radiation dose to the left anterior descending artery by whole and partial breast irradiation in breast cancer patients - Sato, Kazuhiko; Mizuno, Yoshio; Fuchikami, Hiromi; Kato, Masahiro; Shimo, Takahiro; Kubota, Jun; Takeda, Naoko; Inoue, Yuko; Seto, Hiroshi; Okawa, Tomohiko (Journal of Contemporary Brachytherapy, 2015)
Purpose: Breast conserving surgery (BCS) followed by whole breast irradiation (WBI) is the standard of care for breast cancer patients. However, there is a risk of coronary events with WBI therapy. In this study, we compared the radiation dose in the left anterior descending artery (LAD) in patients receiving partial breast irradiation (PBI) with WBI. Material and methods: We evaluated consecutive patients who underwent adjuvant radiotherapy after BCS between October 2008 and July 2014. Whole breast irradiation patients received 50 Gy in fractions of 2 Gy to the entire breast. Partial breast irradiation was performed using multicatheter brachytherapy at a dose of 32 Gy in eight fractions. The mean and maximal cumulative doses to LAD were calculated. The radiotherapeutic biologically effective dose of PBI was adjusted to WBI, and radiation techniques were compared. Results: Of 379 consecutive patients with 383 lesions receiving radiotherapy (151 WBI and 232 PBI lesions), 82 WBI and 100 PBI patients were analyzed. In WBI patients, the mean and maximal cumulative doses for left-sided breast cancer (2.13 ± 0.11 and 8.19 ± 1.21 Gy, respectively) were significantly higher than those for right-sided (0.37 ± 0.02 and 0.56 ± 0.03 Gy, respectively; p < 0.0001). In PBI patients with left-sided breast cancer, the doses for tumors in inner quadrants or central location (2.54 ± 0.21 and 4.43 ± 0.38 Gy, respectively) were significantly elevated compared to outer quadrants (1.02 ± 0.17 and 2.10 ± 0.29 Gy, respectively; p < 0.0001). After the adjustment, the doses in PBI patients were significantly reduced in patients with tumors only in outer quadrants (1.12 ± 0.20 and 2.43 ± 0.37 Gy, respectively; p = 0.0001). Conclusions : Tumor control and dose to LAD should be considered during treatment since PBI may reduce the risk of coronary artery disease especially in patients with lateral tumors in the left breast.